Cortometraje 3D sobre la extinción dinosaurios - Álvarez Gallo, David Gonzalo (2014)
This thesis is a short film of a curious child with many questions about dinosaurs but especially focuses on which were the reasons that led to these creatures to extinction. The film lasts about 5 minutes, using 3D animation and real video, with the main objective to create a realistic integration of these two elements using advanced techniques of digital compositing and post production.